Análise experimental de desempenho térmico de nanofluidos em radiador automotivo - Rodrigues, Nayara Leite (2015)
A new class of refrigerant which nanoparticles are dispersed in a conventional fluid has been studied and promises to revolutionize heat transfer systems, due to high thermal conductivity attributed to these fluids, called nanofluids. In this work, silver nanoparticles were dispersed in a mixture of water / ethylene glycol (70/30 by vol.) In order to analyze the thermal performance applied to an automotive radiator, through the global coefficient of heat transfer. For this purpose, an experimental facilitys was assembled and instrumented, and the nanofluids were produced using a two step method. The tests were conducted in an automotive radiator, in a wind tunnel using samples of the base fluid and nanofluids at concentrations of 0.02% and 0.06 vol.%, in order to compare the two fluids. Besides analyzing the nanofluid behavior at different temperatures of the liquid in this type of application, deposition of nanoparticles was observed in the circuit when operating at temperature of 95 ° C. The results show that nanofluids have an overall heat transfer coefficient below in relation to the base fluid for the same liquid mass flow rate and the same operating conditions, reaching a reduction of 44.1% with the exception of one case, where an increase of 4.9% compared to the base fluid was observed.